Near-Inertial Oscillations of Thermocline in the Shelf Area off Vladivostok, the Sea of Japan, from a Set of Thermostrings - Olga Trusenkova; Igor Yaroshchuk; Alexandra Kosheleva; Aleksandr Samchenko; Alexander Pivovarov; Vyacheslav Dubina (Journal of Marine Science and Engineering)
The shelf area off Vladivostok in the Sea of Japan is known by the intense internal wave activity investigated for many years. The present contribution to these studies is based on data collected on 3–14 October 2022, from four moorings aligned across isobaths and equipped with thermostrings. Multivariate analysis is performed in the depth–time domain, while timescales and directions and speeds of temperature anomaly movement are estimated from wavelet transform. Approximately 50% of the variance results from vertical stratification changes, i.e., thermocline deepening or shoaling, and temperature anomalies on different timescales moved towards the shoaling seafloor. For the first time, near-inertial (NI) oscillations are detected throughout the record and turn out to be the most intense among the 6 to 70 h timescales, moving with the speeds of 0.41–0.55 m/s, although previous attention was paid to the semidiurnal internal tide. A frequency decrease, i.e., red shift, of the NI oscillations is detected towards shallower water, with the frequency eventually becoming subinertial, and is explained by anticyclonic relative vorticity at the eastern side of the mushroom-like structure detected from thermal satellite imagery. The semidiurnal and two-day oscillations were detected, moving with the speeds of 0.95–1.11 and 0.15–1.17 m/s, respectively. The two-day timescale, never reported before, is considered as a difference one caused by nonlinearity. These results are interpreted as the propagation of an internal wave generated at the steep slope offshore to the inner shelf.